DERMATOGLYPHIC PROFILE SOMATOTYPICAL IN ATHLETES AND SWIMMERS OF 8 TO 12 YEARS (Fiep Bulletin - online, 2013)
Some questions leave us puzzled: "What makes an athlete better than another?" There are several questions that encourage us to seek answers to the appropriation of a definite talent for sport. In order to change the shape of empirical scientific method selection arises. The aim of this study was to evaluate the profile of athletes somatotypical dermatoglyphic and basic swimming in the age group 8-12 years. The sample consisted of 33 subjects of both sexes between 8 and 12 years, team members based C3's Swim School in the city of Joinville, Santa Catarina. The research instruments were used: protocol dermatoglyphic Cummins & Midlo, protocol somatotype and Heath & Carter equation for the final height. The male group (n = 19) studied had a mean age of 11.3 ± 1.2 years, body weight 45.5 ± 12.55 kg, height 149.9 ± 13.1 cm; somatotipica feature: Endomorphy (5, 5 ± 2.29); Mesomorphy (3.5 ± 1.87) and ectomorphic (2.7 ± 1.80). Dematoglíficas Feature: Arc (0.8 ± 1.89), Hook (6.7 ± 2.53) and whorl (2.4 ± 2.52). The female group (n = 14) studied had a mean age of 11.4 ± 0.89 years, body weight 49.6 ± 16.40 kg, height 150.9 ± 13.1 cm; somatotype: Endomorphy (5.2 ± 2.33); Mesomorphy (3.0 ± 2.10) and ectomorphic (2.2 ± 1.85). How dermatoglyphic average found Arco (0.8 ± 1.31), Hook (6.7 ± 2.55) and whorl (2.5 ± 2.90). We conclude that the genetic capacity is a determining factor for the success of the athlete and rare among those who practice the sport within the study did not receive sugeitos with characteristic referenced in the literature. As Ulrich (1973, apud Weineck, 2005) only 6% of all individuals in a normal distribution within the population, have a high value, above average in some characteristic. Being found in little groups wishing to stay in the sports arena, with successful athletes.
Keywords: Dermatoglyphics; somatotype; swimming